Global Landscape of Qur’anic Studies (2000–2025): Science Mapping, Collaboration, and Thematic Evolution - Judijanto, Loso; Fatahillah, Wilnan; Luhur, Mujhid Budi; Rusdi, Imam; Uska, Dedi; Sudarmanto, Eko (Westscience Press, 2026)
The research is focused on the investigation of the global development of Qur’anic studies between 2000 and 2025 through a bibliometric analysis and a science mapping approach. For data collection and analysis, a database of Scopus was utilized with the use of VOSviewer software tools. The results show that there was consistent growth in the number of publications in the field. The most noticeable feature is that many contributions came from South East Asian countries like Indonesia and Malaysia, becoming the key centers for international cooperation in scientific research. Moreover, based on the analysis of co-authorship networks, one can note that the existing system was relatively clustered, implying the existence of well-established research communities in the regions with few connections between the regions. At the same time, the citation analysis reveals the multidisciplinary character of the research area and its interlinkage with many aspects of theological, ethic, gender, health, and socio-economic studies. In addition, the analysis of keyword co-occurrences and overlay networks shows that apart from classic keywords such as 'tafsir' and 'exegesis,' digital humanities and computation approaches also gained popularity. This study underscores the evolving and interdisciplinary character of Qur’anic studies and highlights the need for stronger international collaboration and methodological innovation to enhance its global academic impact.